2021
DOI: 10.1158/0008-5472.can-20-1417
|View full text |Cite
|
Sign up to set email alerts
|

BRD9 Is a Critical Regulator of Androgen Receptor Signaling and Prostate Cancer Progression

Abstract: Switch/sucrose-nonfermentable (SWI/SNF) chromatin-remodeling complexes are critical regulators of chromatin dynamics during transcription, DNA replication, and DNA repair. A recently identified SWI/SNF subcomplex termed GLTSCR1/1L-BAF (GBAF; or “noncanonical BAF”, ncBAF) uniquely contains bromodomain-containing protein BRD9 and glioma tumor suppressor candidate region 1 (GLTSCR1) or its paralog GLTSCR1-like (GLTSCR1L). Recent studies have identified a unique dependency on GBAF (ncBAF) complexes in synovial sar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 64 publications
4
61
0
Order By: Relevance
“…The use of md method is a new way to identify interaction between homologous as well as non-homologues proteins on the basis of atom-to-atom alignment profile between two interacting proteins. The computational approach with md has been used to demonstrate mode of action of natural compound as possible drug and therapeutics in cancer [22] , [23] . Recently, therapeutic importance of human antimicrobial peptide LL-37 for COVID has been analyzed by md methods [24] .…”
Section: Consequences Of the Hypothesis And Discussionmentioning
confidence: 99%
“…The use of md method is a new way to identify interaction between homologous as well as non-homologues proteins on the basis of atom-to-atom alignment profile between two interacting proteins. The computational approach with md has been used to demonstrate mode of action of natural compound as possible drug and therapeutics in cancer [22] , [23] . Recently, therapeutic importance of human antimicrobial peptide LL-37 for COVID has been analyzed by md methods [24] .…”
Section: Consequences Of the Hypothesis And Discussionmentioning
confidence: 99%
“…Smith's paper on BRD9 in PCa suggests BRD9 could play a role in CRPC with BRD9 knockdown reducing the viability of AR-positive cell lines (including castration-resistant cell lines) [30]. Here, this cell line data was further characterised in 2053 PCa patients and did not suggest as promising a role, given BRD9 expression was similar in patients treated with and without second-generation antiandrogens.…”
Section: Brd9 and Crpcmentioning
confidence: 92%
“…BRD9 has not been well studied in prostate cancer to date with one paper published in December 2020 [30]. This paper showed that BRD9 inhibition and knockdown have overlapping effects, reducing AR-positive cell line growth both in vivo and in vitro.…”
Section: Brd9 and Pcamentioning
confidence: 99%
See 2 more Smart Citations